PELATIHAN TEKNIK FLOWCHARTING DALAM MEMBANGUN LOGIKA DASAR SISWA DI SEKOLAH ALAM SAKA KEDIRI - Puspoko Ponco Ratno; Kadi (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The flowcharting training at Sekolah Alam SAKA Kediri was initiated to address the need for enhancing students’ logical and systematic thinking skills, which were still limited. Flowcharting was chosen for its effectiveness in visualizing thought processes, facilitating problem analysis, and strengthening basic logic. This community service activity applied the Asset Based Community Development (ABCD) method through stages of discovering potential, envisioning goals, designing programs, connecting assets, and conducting evaluations. The training included socialization, learning flowchart symbols and structures, hands-on practice at school and on campus, and intensive mentoring. As a result, students gained a basic understanding of flowcharting concepts, were able to create simple flow diagrams, and demonstrated improvements in logical thinking, problem-solving skills, and structured thinking habits. Feedback from teachers and students indicated that the program was beneficial and has the potential to provide long-term impacts on students’ academic achievement and 21st-century skills.